Atividade inseticida de espécies de trichilia frente à lagarta-do-cartucho do milho spodoptera frugiperda - Nebo, Liliane (2008)
This work presents the phytochemical study and biological assays carried out with organic extracts of fruits and seeds from Trichilia claussenii, T. elegans and inflorescence from T. catigua against S. frugiperda. Among the extracts assayed, the methanol extracts of seeds from T. claussenii and inflorescence from T. catigua presented the highest insecticidal activity, with 64,0 and 64,4 % of mortality, respectively. The bioassay-guided study of the methanol extract of seeds from T. claussenii led to identification of -phenylalkyl and alkenyl fatty acids, active substances in this extract. The flavonoid ent-catequin was isolated from the methanol extract of inflorescence from T. catigua and it was associated with the insecticidal activity found in this extract. Fatty acids with the methylene chains ranging from C-5 to C-16 were assayed against S. frugiperda. Tests showed that the hexanoic, nonanoic and decanoic acids, displayed the highest rate of mortality at concentration of 10,0 mg/mL. The study of the three species allowed isolating and identifying the following compounds: a mixture of -phenylalkyl and alkenyl fatty acids, -lactonas, 4-hydroxy-N-methylproline, N-methylproline, uridine, uracile, entcatequin, 5-O-cafeoylquinic acid and the steroids 3--O--Dglucopyranosilsitosterol, -sitosterol, campesterol, estigmasterol e sitostenone. The limonoids 11-acetoxyobacunone and 1,2-dihiyro-1-acetoxy-11-acetoxy-14,15-epoxycneorin R were isolated for the first time from a Trichilia species.